Heat-conducting, high-temperature-insulating and fire-resistant ceramic tape as well as preparation method and application thereof
By modifying the surface of inorganic thermally conductive fillers and ceramicized fillers and using specific ratios of inorganic thermally conductive fillers, the high temperature fire and electricity protection problem of lithium-ion batteries in extreme operating conditions is solved, and the high insulation resistance and thermal conductivity of ceramic tapes are achieved, reducing the preparation cost.
Patent Information
- Application Number
- CN202411814157.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to meet the high temperature fire and electricity protection requirements of lithium-ion batteries under extreme operating conditions, and the preparation process is complex and costly.
The surface of the inorganic thermally conductive filler is modified by a monoalkoxy titanate coupling agent, and the surface of the inode ceramicized filler is modified by a chelated titanate coupling agent to improve the high-temperature insulation performance; inorganic thermally conductive filler such as alumina, aluminum hydroxide and boron nitride are used to form a tight thermally conductive path to improve thermally conductive properties.
The high-temperature insulation and thermal conductivity of ceramic tapes under extreme operating conditions is achieved, which meets the needs of high insulation resistance and thermal conductivity, while reducing the preparation cost.
Smart Images

Figure BDA0005181312610000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic tapes, and in particular to a heat-conducting, high-temperature insulating, refractory ceramic tape and a preparation method and application thereof. Background Art
[0002] In recent years, with the vigorous development of the new energy vehicle industry, the market has greatly increased the endurance and charging efficiency of power batteries, so high rate, high capacity and good cycle performance are the main development trends of lithium batteries. As the energy density of lithium-ion power batteries increases, the battery life is extended, and there are more and more incidents of lithium-ion battery spontaneous combustion and explosion; thermal runaway may occur under conditions of overcharging, short circuit, high temperature, impact, etc., which will instantly release a large amount of heat, causing fires or even explosions, causing huge losses to related companies and users.
[0003] Therefore, automobile manufacturers are paying more and more attention to thermal management materials for power batteries, especially multifunctional materials that can be used for daily heat conduction and insulation, insulation after high temperatures and high temperature resistance.
[0004] Patent CN 116004129A discloses a ceramic composite tape for fireproof and high-temperature insulation of power batteries, and its preparation and application, wherein the ceramic glue contains the following components by mass percentage: 30-48% inorganic ceramic filler, 20-30% inorganic flame retardant filler, 30-48% organic silicon material, 1-2% cross-linking agent and 0.3-1% auxiliary agent. The conventional thermal conductivity of the composite tape is low. Although it has certain electrical insulation performance after high temperature, the insulation resistance is greater than 0.5MΩ, but it is not enough to meet the market's increasingly high electrical insulation performance requirements (insulation resistance>15GΩ).
[0005] Patent CN 118572319A discloses a ceramic silicone rubber composite tape, which is a double-layer structure. The first layer is a functional layer formed by curing ceramic liquid silicone rubber, and the second layer is a glass fiber cloth. The raw materials of the functional layer include addition liquid silicone rubber, platinum catalyst and ceramic composite powder coated with platinum. After the surface of the ceramic composite powder is coated with platinum, it has a synergistic effect with the platinum catalyst to improve the flame retardant and porcelain-forming properties of the ceramic silicone rubber composite tape, so that the product can further improve the flame retardant and porcelain-forming properties while ensuring excellent mechanical properties. The obtained product is wrapped around the copper busbar of the high-voltage connector in the battery pack of new energy vehicles, which plays a role in fire prevention and insulation. Although this method improves the high-temperature insulation resistance>500MΩ, it cannot meet the requirements of insulation resistance>15GΩ, and has no thermal conductivity. At the same time, various pretreatments are required during the preparation process, and the manufacturing cost is high. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a thermally conductive high-temperature insulating refractory ceramic belt and a preparation method and application thereof. The surface of an inorganic thermally conductive filler is modified by a monoalkoxy titanate coupling agent, and the surface of an inorganic ceramic filler is modified by a chelate titanate coupling agent to improve the high-temperature insulation performance. Alumina, aluminum hydroxide and boron nitride are used as the inorganic thermally conductive filler in a suitable ratio to form a thermally conductive path with closer contact, thereby improving the thermal conductivity. The inorganic thermally conductive filler and the inorganic ceramic filler form a stable skeleton structure at high temperature, thereby further improving the high-temperature insulation performance.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a thermally conductive high-temperature insulating refractory ceramic tape, comprising a glass fiber layer, and a fire-resistant organic coating coated on both sides of the glass fiber layer, wherein the fire-resistant organic coating comprises the following raw material components by weight:
[0008] 40-50 parts of inorganic thermal conductive filler, 25-35 parts of inorganic ceramic filler, 20-30 parts of silicone rubber, 0.5-1 parts of curing agent, 0.5-1.5 parts of coupling agent, 0.3-0.5 parts of reaction aid, 50-150 parts of solvent.
[0009] Furthermore, the organic silicone rubber is one or more of methyl vinyl silicone oil, methyl vinyl phenyl silicone oil, and methyl vinyl silicone rubber, preferably methyl vinyl silicone oil. The molecular weight of the organic silicone rubber is 500-60000, and the vinyl content is 0.03-3.5%.
[0010] Furthermore, the curing agent includes hydrogen-containing silicone oil, and the hydrogen content of the hydrogen-containing silicone oil is 0.18-1.5%.
[0011] The invention enhances the strength and impact resistance of the fireproof organic coating by reacting vinyl organic silicon rubber with hydrogen-containing silicone oil.
[0012] Furthermore, the coupling agent includes a monoalkoxy titanate coupling agent and a chelate titanate coupling agent.
[0013] The present invention modifies the surface of inorganic thermal conductive filler powder by using a monoalkoxy titanate coupling agent, so that a monomolecular film is formed on the surface of the powder, and no multimolecular film exists on the interface, thereby enhancing its compatibility in silica gel and further reducing the gaps between powder particles, thereby becoming denser, and being easier to fill, bond, and copolymerize and crystallize after the glass powder is melted under a high-temperature environment; the surface of the inorganic ceramic filler powder is modified by using a chelated titanate coupling agent, so that the moisture on the surface of such high-humidity powder can be fully consumed, and compared with traditional treatment agents, the moisture in the material is better reduced, thereby reducing the ablation rate at high temperature, further improving the ceramic compactness of the ultra-thin thickness at high temperature, and enhancing the high-temperature insulation performance.
[0014] Further, the inorganic thermal conductive filler includes aluminum oxide, aluminum hydroxide and boron nitride in a mass ratio of 1: (0.2-0.8): (0.02-0.2); for example: 1:0.5:0.1, 1:0.5:0.03, 1:0.4:0.1, 1:0.6:0.1, etc., including but not limited to this;
[0015] The aluminum oxide and aluminum hydroxide have a D50 particle size of ≤20 μm and a D90 particle size of ≤50 μm;
[0016] The boron nitride has a D50 particle size of ≤5 μm and a D90 particle size of ≤50 μm.
[0017] Further, the non-polar ceramic filler includes kaolin, fumed silica and wollastonite in a mass ratio of 1:(1-2):(0.5-1); for example: 1:1:0.5, 1:1:1, 1:1.5:1, 1:1.5:0.5, 1:2:0.5, etc., including but not limited to these;
[0018] The D50 particle size of the non-polar ceramic filler is ≤10 μm, and the D90 particle size is ≤50 μm;
[0019] The specific surface area of the fumed silica is 100-200m 2 / g.
[0020] The present invention forms a heat-conducting path with closer contact by compounding three kinds of heat-conducting fillers, namely, medium-sized high-temperature-resistant alumina, small-sized boron nitride and medium-sized aluminum hydroxide, which is helpful to improve its thermal conductivity; by introducing alumina and boron nitride that still maintain a complete crystalline structure after high temperature, and more alumina introduced by high-temperature decomposition of kaolin into mullite, together constitute the skeleton of the green body strength; at the same time, multiple particle sizes and multiple particle forms are combined and aggregated, and the ceramic shell structure is enriched under the joint action, which greatly enhances its electrical insulation performance after high temperature; in addition, aluminum hydroxide can not only improve its thermal conductivity and flame retardant performance, but the alumina formed after high-temperature dehydration can be better combined with alumina, and under the high-temperature sintering filling of kaolin, gas-phase silica and wollastonite, they can enrich the ceramic shell structure together to make it denser, so that it has high insulation performance; in addition, by strictly controlling the particle size of inorganic heat-conducting fillers and inorganic ceramic fillers, it is ensured that they can be made into a thinner thickness for easy winding.
[0021] Furthermore, the reaction aid comprises an alkynol inhibitor and a Pt catalyst, and the Pt content of the Pt catalyst is 1000-3000 ppm.
[0022] Furthermore, the solvent is one or more of ethyl acetate, toluene, xylene, petroleum ether, and 120# solvent oil.
[0023] Further, the thickness of the glass fiber layer is 0.03-0.4 mm, for example: 0.03 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, etc., including but not limited to these;
[0024] And / or, the thickness of the fireproof organic coating is 0.03-0.3 mm, for example: 0.03 mm, 0.04 mm, 0.08 mm, 0.1 mm, 0.2 mm, 0.25 mm, 0.3 mm, etc., including but not limited to the above. The thickness of the glass fiber layer and the fireproof organic coating is adjusted according to the process and raw materials to meet the application scenario of ultra-thin winding inside the battery.
[0025] Furthermore, the thickness of the ceramic tape is 0.1-0.5 mm, such as 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, etc., including but not limited to these.
[0026] The second aspect of the present invention provides a method for preparing the thermally conductive high-temperature insulating refractory ceramic tape according to the first aspect, comprising the following method:
[0027] S1. Mix the silicone rubber and the chelated titanate coupling agent uniformly at 80-100°C (for example, 80°C, 85°C, 90°C, 95°C, 100°C, etc., including but not limited to these);
[0028] S2, maintaining the temperature at 80-100°C, adding inorganic ceramic filler and continuing to mix evenly;
[0029] S3, maintaining the temperature at 80-100°C, adding monoalkoxy titanate coupling agent and inorganic thermal conductive filler and continuing to mix evenly;
[0030] S4, cool down to below 45°C, add hydrogenated silicone oil and acetylene alcohol inhibitor and mix well;
[0031] S5, keeping the temperature below 45°C, adding Pt catalyst and solvent and mixing evenly to form a fire-retardant organic coating coating liquid;
[0032] S6. Apply fire-retardant organic coating on both sides of the glass fiber layer by a coating machine.
[0033] Furthermore, in S1-S5, the mixing is carried out in a kneader, and the mixing time is independently selected from 30-60 min.
[0034] The third aspect of the present invention provides an application of the thermally conductive high-temperature insulating refractory ceramic tape described in the first aspect in a new energy power battery.
[0035] Beneficial effects of the present invention:
[0036] The ceramic tape of the present invention has the characteristics of thermally conductive silicone tape at room temperature, is a flexible thermally conductive material, and can be used as a thermal management material. When the battery pack faces thermal runaway under extreme working conditions and faces rapidly rising temperatures, the thermally conductive high-temperature insulating refractory ceramic tape quickly loses water and takes away part of the heat, while immediately forming a sufficiently dense ceramic shell structure to prevent the spread of flames. At the same time, it has extremely high insulation resistance and will not conduct electricity under the extremely high voltage that may be generated by the battery pack runaway, thereby meeting the market's requirements for high-temperature fire and electrical protection of ceramic tapes under extreme working conditions. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment relates to a method for preparing a thermally conductive high-temperature insulating refractory ceramic tape, comprising the following steps:
[0040] (1) 9 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 11.3 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0041] (2) Maintaining a high temperature of 80°C, add 10 parts (1.5 μm D50\45 μm D90) kaolin, 5 parts (3 μm D50\45 μm D90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0042] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 30 parts (5 μmD50\40 μmD90) of aluminum oxide, 15 parts (2 μmD50\30 μmD90) of aluminum hydroxide, and 3 parts (2 μmD50\40 μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0043] (4) Cooling the temperature to below 45°C, adding 0.6 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0044] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 100 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0045] (6) Using a 0.1 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.4 mm.
[0046] Example 2
[0047] This embodiment relates to a method for preparing a thermally conductive high-temperature insulating refractory ceramic tape, comprising the following steps:
[0048] (1) 19 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 5.1 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0049] (2) Maintaining a high temperature of 80°C, add 10 parts (1.5 μm D50\45 μm D90) kaolin, 5 parts (3 μm D50\45 μm D90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0050] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 28 parts (5 μmD50\40 μmD90) of aluminum oxide, 12 parts (2 μmD50\30 μmD90) of aluminum hydroxide, and 3 parts (2 μmD50\40 μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0051] (4) Cooling the temperature to below 45°C, adding 0.8 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0052] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 100 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0053] (6) Using a 0.1 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.3 mm.
[0054] Example 3
[0055] This embodiment relates to a method for preparing a thermally conductive high-temperature insulating refractory ceramic tape, comprising the following steps:
[0056] (1) 19 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 8 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0057] (2) Maintaining a high temperature of 80°C, add 8 parts (1.5 μmD50\45 μmD90) kaolin, 4 parts (3 μmD50\45 μmD90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0058] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 28 parts (5 μmD50\40 μmD90) of aluminum oxide, 14 parts (2 μmD50\30 μmD90) of aluminum hydroxide, and 1 part (2 μmD50\40 μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0059] (4) Cooling the temperature to below 45°C, adding 0.9 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0060] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 70 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0061] (6) Using a 0.05 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.15 mm.
[0062] Comparative Example 1
[0063] This comparative example relates to a method for preparing a ceramic tape, which does not add boron nitride compared to Example 1, and specifically comprises the following steps:
[0064] (1) 9 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 11.3 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0065] (2) Maintaining a high temperature of 80°C, add 10 parts (1.5 μm D50\45 μm D90) kaolin, 5 parts (3 μm D50\45 μm D90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0066] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 30 parts (5 μmD50\40 μmD90) of aluminum oxide, and 15 parts (2 μmD50\30 μmD90) of aluminum hydroxide, and continue stirring for 40 minutes to mix evenly;
[0067] (4) Cooling the temperature to below 45°C, adding 0.6 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0068] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 100 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0069] (6) Using a 0.1 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.4 mm.
[0070] Comparative Example 2
[0071] This comparative example relates to a method for preparing a ceramic belt, which reduces the amount of aluminum oxide added compared to Example 1, and comprises the following steps:
[0072] (1) 9 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 11.3 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0073] (2) Maintaining a high temperature of 80°C, add 10 parts (1.5 μm D50\45 μm D90) kaolin, 5 parts (3 μm D50\45 μm D90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0074] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 5 parts (5μmD50\40μmD90) of aluminum oxide, 15 parts (2μmD50\30μmD90) of aluminum hydroxide, and 3 parts (2μmD50\40μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0075] (4) Cooling the temperature to below 45°C, adding 0.6 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0076] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 100 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0077] (6) Using a 0.1 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.4 mm.
[0078] Comparative Example 3
[0079] This comparative example relates to a method for preparing a ceramic tape, which changes the type of coupling agent compared to Example 2, and comprises the following steps:
[0080] (1) 19 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 5.1 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of silane coupling agent KH570 were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0081] (2) Maintaining a high temperature of 80°C, add 10 parts (1.5 μm D50\45 μm D90) kaolin, 5 parts (3 μm D50\45 μm D90) wollastonite, and 15 parts (specific surface area 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0082] (3) Maintaining a high temperature of 80°C, add 0.4 parts of silane coupling agent KH570, 28 parts (5μmD50\40μmD90) of aluminum oxide, 12 parts (2μmD50\30μmD90) of aluminum hydroxide, and 3 parts (2μmD50\40μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0083] (4) Cooling the temperature to below 45°C, adding 0.8 parts of hydrogen-containing silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0084] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 100 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0085] (6) Using a 0.1 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.3 mm.
[0086] Comparative Example 4
[0087] This comparative example relates to a method for preparing a ceramic tape, which changes the type of inorganic ceramic filler compared to Example 3, and comprises the following steps:
[0088] (1) 19 parts of methyl vinyl silicone oil with a vinyl content of 0.42% and a molecular weight of 5000, 8 parts of methyl vinyl silicone oil with a vinyl content of 0.22% and a molecular weight of 30000, and 0.35 parts of a chelate titanate coupling agent were added to a kneader, heated to 80° C. and stirred for 30 minutes to mix evenly;
[0089] (2) Maintaining a high temperature of 80°C, add 8 parts (1.5 μmD50\45 μmD90) of clay, 4 parts (3 μmD50\45 μmD90) of wollastonite, and 15 parts of a specific surface area of 150 m 2 / g of fumed silica and continue stirring for 30 minutes to mix evenly;
[0090] (3) Maintaining a high temperature of 80°C, add 0.4 parts of monoalkoxy titanate coupling agent, 28 parts (5 μmD50\40 μmD90) of aluminum oxide, 14 parts (2 μmD50\30 μmD90) of aluminum hydroxide, and 1 part (2 μmD50\40 μmD90) of boron nitride, and continue stirring for 40 minutes to mix evenly;
[0091] (4) Cooling the temperature to below 45°C, adding 0.9 parts of hydrogenated silicone oil with a hydrogen content of 0.4% and 0.05 parts of acetylene alcohol inhibitor, stirring for 30 minutes, and mixing evenly;
[0092] (5) Keeping the temperature below 45°C, add 0.3 parts of 2000 ppm pt catalyst and 70 parts of solvent, stir for 30 minutes to mix evenly, and use it as the fire-retardant organic coating coating liquid;
[0093] (6) Using a 0.05 mm glass fiber layer as the base film, a fire-retardant organic coating is applied on both sides of the base film by a coating machine until the total thickness of the ceramic tape is 0.15 mm.
[0094] The performance tests were performed on the ceramic tapes prepared in Examples 1-3 and Comparative Examples 1-4. The results are shown in Table 1.
[0095] The test conditions are:
[0096] 1. High temperature insulation resistance: The insulation resistance of the ceramic tape is tested after being placed in a muffle furnace at 800℃ for 30 minutes, with the condition of DC1000V / 60s.
[0097] 2. Porcelain properties: After the ceramic tape is baked at 800℃ in a muffle furnace for 30 minutes, observe whether there are cracks, bulges or delamination on the surface.
[0098] 3. Thermal conductivity: thermal conductivity tester.
[0099] Table 1
[0100]
[0101] It can be seen from Table 1 that the ceramic tapes prepared in Examples 1-3 of the present invention all have excellent high-temperature insulation resistance, all greater than 15 GΩ, among which the insulation resistance of the ceramic tape prepared in Example 1 is as high as 23.12 GΩ. At the same time, the ceramic tape has excellent thermal conductivity and porcelain-forming properties.
[0102] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that less boron nitride and aluminum oxide are added in Comparative Examples 1 and 2, respectively, and the high-temperature insulation resistance is significantly reduced. This is because the appropriate proportion of aluminum oxide and boron nitride in Example 1, and the decomposition of kaolin into mullite introduces more aluminum oxide, which together construct the body skeleton and greatly enhance its electrical insulation performance after high temperature.
[0103] From the comparison between Example 2 and Comparative Example 3, it can be seen that the high-temperature insulation resistance of Comparative Example 3 is greatly reduced. This is because the KH570 coupling agent used in Comparative Example 3 cannot reduce the gap between powders and cannot consume the moisture between powders, resulting in the shell being not dense enough after ceramicization and the high-temperature insulation resistance being low.
[0104] From the comparison between Example 3 and Comparative Example 4, it can be seen that Comparative Example 4 has obvious cracking, because the kaolin in Comparative Example 4 is replaced with clay. Compared with clay, kaolin decomposes into mullite and introduces more alumina, which constitutes the skeleton of the green body strength. The ceramic shell structure has higher strength and is less prone to cracking.
[0105] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A thermally conductive high temperature insulating refractory ceramic belt, characterized in that: It comprises a glass fiber layer and a fire-proof organic coating coated on both sides of the glass fiber layer. The fire-proof organic coating comprises the following raw material components by weight: 40-50 parts of inorganic thermal conductive filler, 25-35 parts of inorganic ceramic filler, 20-30 parts of silicone rubber, 0.5-1 parts of curing agent, 0.5-1.5 parts of coupling agent, 0.3-0.5 parts of reaction aid, 50-150 parts of solvent.
2. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The organic silicone rubber is one or more of methyl vinyl silicone oil, methyl vinyl phenyl silicone oil and methyl vinyl silicone rubber raw rubber.
3. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The curing agent includes hydrogen-containing silicone oil, and the hydrogen content of the hydrogen-containing silicone oil is 0.18-1.5%.
4. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The coupling agent includes a monoalkoxy titanate coupling agent and a chelate titanate coupling agent.
5. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The inorganic thermal conductive filler comprises aluminum oxide, aluminum hydroxide and boron nitride in a mass ratio of 1: (0.2-0.8): (0.02-0.2); The aluminum oxide and aluminum hydroxide have a D50 particle size of ≤20 μm and a D90 particle size of ≤50 μm; The boron nitride has a D50 particle size of ≤5 μm and a D90 particle size of ≤50 μm.
6. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The non-polar ceramic filler comprises kaolin, fumed silica and wollastonite in a mass ratio of 1:(1-1.5):(0.5-1); The D50 particle size of the non-polar ceramic filler is ≤10 μm, and the D90 particle size is ≤50 μm; The specific surface area of the fumed silica is 100-200m 2 / g.
7. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The reaction aid comprises an alkynol inhibitor and a Pt catalyst.
8. The thermally conductive high temperature insulating refractory ceramic tape according to claim 1, characterized in that: The thickness of the glass fiber layer is 0.03-0.4 mm; And / or, the thickness of the fire-retardant organic coating is 0.03-0.3 mm.
9. A method for preparing the thermally conductive high temperature insulating refractory ceramic tape according to any one of claims 1 to 8, characterized in that: The following methods are included: S1. Mix the silicone rubber and chelated titanate coupling agent evenly at 80-100°C; S2, maintaining the temperature at 80-100°C, adding inorganic ceramic filler and continuing to mix evenly; S3, maintaining the temperature at 80-100°C, adding monoalkoxy titanate coupling agent and inorganic thermal conductive filler and continuing to mix evenly; S4, cool down to below 45°C, add hydrogenated silicone oil and acetylene alcohol inhibitor and mix well; S5, keeping the temperature below 45°C, adding Pt catalyst and solvent and mixing evenly to form a fire-retardant organic coating coating liquid; S6. Apply fire-retardant organic coating on both sides of the glass fiber layer by a coating machine.
10. Use of the thermally conductive high-temperature insulating refractory ceramic tape according to any one of claims 1 to 8 in new energy power batteries.
Citation Information
Cited By
Battery pack ceramic composite belt and preparation method thereof
CN120574484A